Switching to fast growth: the insulin-like growth factor (IGF) system in skeletal muscle of Atlantic salmon. - Bower, Neil Ivan; Li, Xuejun; Taylor, R; Johnston, Ian Alistair (Journal of Experimental Biology, 2008)
In this study we describe the complete coding sequence for insulin-like growth factor I (IGF-I), insulin-like growth factor II (IGF-II), insulin-like growth factor binding protein (IGFBP) 1, 2, 4, 5 and 6 and IGFBP-related protein 1 (IGFBP-rP1) of Atlantic salmon (Salmo salar L.). We also report the characterisation of two gene paralogues of IGFBP-2 and IGFBP-5. Following 22 days restricted feeding (0d) to achieve zero growth, fish were fed to satiation and sampled at 3, 5, 7, 14, 30 and 60 days. Expression profiles for genes involved in the IGF signalling pathway in fast myotomal muscle were determined using real-time quantitative RT-PCR. The transition from zero to fast growth is characterised by constitutive upregulation of IGF-I and IGFBP-4, a transient increase in IGFBP-5.2, and downregulation of IGFBP-2.1, IGF-II, IGF2R (IGF-II receptor) and IGFR1a (IGF-I receptor a). Expression of IGFBP-2.2, IGFBP-5.1, IGFBP-6, IGFBP-rP1 and IGFR1b showed little or no response to feeding. Expression of the myogenic marker genes myogenin, MHC and MLC2 were higher with feed restriction, and decreased as an early response to feeding, before increasing to a peak at 14 days, corresponding with a peak in IGF-I expression. IGFBP-4, which contains a putative connective tissue localisation signal, was the only IGFBP constitutively upregulated following feeding, and was positively correlated with IGF-I expression. Together, these data show that switching to fast growth in Atlantic salmon skeletal muscle involves the local upregulation of IGF-I, IGFBP-5.2 and IGFBP-4, with downregulation of IGFBP-2.1.